2023
DOI: 10.1093/asj/sjad260
|View full text |Cite
|
Sign up to set email alerts
|

Large Language Models and Artificial Intelligence: A Primer for Plastic Surgeons on the Demonstrated and Potential Applications, Promises, and Limitations of ChatGPT

Abstract: Background The rapidly evolving field of artificial intelligence (AI) holds great potential for plastic surgeons. ChatGPT, a recently released AI large language model (LLM), promises application across many disciplines, including healthcare. Objectives The aim of this article is to provide a plastic surgeon’s primer on AI, LLM, and ChatGPT, including an analysis of current demonstrated and proposed clinical applications. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 195 publications
0
5
0
Order By: Relevance
“…The speed at which an LLM can respond to queries becomes irrelevant if it offers incorrect and potentially harmful recommendations. Misinformation can lead to adverse patient outcomes and the erosion of trust in technology and healthcare providers [9,57,60]. As previously mentioned, we acknowledge that neither ChatGPT nor Gemini was designed specifically with medical applications in mind.…”
Section: Limitationsmentioning
confidence: 98%
See 2 more Smart Citations
“…The speed at which an LLM can respond to queries becomes irrelevant if it offers incorrect and potentially harmful recommendations. Misinformation can lead to adverse patient outcomes and the erosion of trust in technology and healthcare providers [9,57,60]. As previously mentioned, we acknowledge that neither ChatGPT nor Gemini was designed specifically with medical applications in mind.…”
Section: Limitationsmentioning
confidence: 98%
“…Two publicly available LLMs that have garnered recent interest are Google's Gemini [7] (built upon its predecessor Bard) and OpenAI's ChatGPT [8]. Although not designed specifically for medical purposes, these LLMs have demonstrated potential in medical decision making [9]. For example, ChatGPT achieved passing scores for both the United States Medical Licensing Examination [10] and American Society for Surgery of the Hand self-assessment exam [11], demonstrating a basic level of competence in medical 2 of 14 reasoning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review in 2023 found 13 articles reporting plastic-surgery-related applications of ChatGPT, demonstrating the emerging interest in the field of implementing this novel technology. 16 One study assessed the accuracy of ChatGPT in answering diverse medical queries. 17 Similar to our study, the generated responses were graded by physicians in terms of accuracy and comprehensiveness and found to be nearly completely correct in both categories, even in complex topics.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[18][19][20][21] There remain appropriate concerns over the limitations of AI programs, including imperfect accuracy of generated outputs and the potential of AI programs working with out-ofdate information. [22][23][24] Although no plastic-surgery-specific AI tool has been developed, various companies have produced generative AI tools that are readily accessible by the general public. The long-term aim of this research is to determine the functionality and reliability of incorporating AI as a clinical tool to help manage patient questions and clinical concerns in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%